A prescription model for vapes: the way we 'do' medicines policy in Australia - Michelle Scollo; Claire Grace; Tanya Buchanan; Anita Dessaix (Sax Institute, 2024)
On 2 May 2023, the Australian Federal Government announced a suite of reforms aimed at ensuring the effectiveness of the prescription model of regulation of vaping (or e-cigarette) products in Australia. These reforms are intended to protect Australians, particularly young people, from the harms of vaping and nicotine dependence. The ensuing public debate on the issue has often created the impression that the options under consideration are to either retain 'recently introduced' prescription regulation or to 'revert to' a retail supply approach. However, the sale of nicotine vapes by retailers such as tobacconists and convenience stores has never been lawful in Australia. The reforms do not seek to change the way nicotine vaping products are regulated, but rather to ensure that the existing prescription model can be effectively enforced and can function as originally intended. This paper describes the historical context and rationale for strengthening prescription regulation of vapes in this country.